Efisiensi Pembayaran Digital melalui QRIS pada UMKM Tasikmalaya - Kusnandar, Deasy Lestary; Sari, Dewi Permata; Sahroni, Nana (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
This research aims to find out whether the perceived usefulness of QRIS and the convenience of QRIS influence the efficiency of digital payments in Tasikmalaya MSMEs. This study uses a quantitative approach. The sample in this research was 100 MSMEs in Tasikmalaya City. The sampling technique used in this research was Non Probability Sampling using purposive sampling. The data collection technique in this research is by using a questionnaire. Data processing and analysis techniques are validity testing, reliability testing, multiple regression analysis and hypothesis testing. The results of this research show that perceived usefulness and perceived convenience influence the efficiency of digital payments using QRIS for MSMEs in the city of Tasikmalaya.